Communication Strategy of the English Goes to Kampung Team in Cultural Adaptation - Natalia, El Chris (Communicare : Journal of Communication Studies, 2023)
English Goes to Kampung (EGK) is a non-profit organization that provides education and workshop to rural society in Sumba, East Nusa Tenggara, Indonesia. The aim of this study is to analyze the communication strategy in cultural adaptation carried out by the EGK team for the society in Sumba villages. The main theory used in this study is the theory of communication accommodation. The research method used is descriptive qualitative analysis. Data was collected through in-depth interviews with three informants of the EGK team. The results show that informants are more likely to adopt a convergence strategy in adapting to the society in the village they visited. This convergence strategy is an effort to approach the villagers so that the EGK team can be accepted and the activities they will do in the village can be done properly.